2020
DOI: 10.1515/nanoph-2020-0521
|View full text |Cite
|
Sign up to set email alerts
|

Double moiré localized plasmon structured illumination microscopy

Abstract: Structured illumination microscopy (SIM) is a well-established fluorescence imaging technique, which can increase spatial resolution by up to a factor of two. This article reports on a new way to extend the capabilities of structured illumination microscopy, by combining ideas from the fields of illumination engineering and nanophotonics. In this technique, plasmonic arrays of hexagonal symmetry are illuminated by two obliquely incident beams originating from a single laser. The resulting interference between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Electron beam lithography (EBL), a technique renowned for its precision in crafting custom designs on lithographic resists, plays a crucial role in this process. In the context of LPSIM, EBL has been employed to create hexagonal arrays of silver nanodisks on glass substrates, subsequently coated with a thin layer of polymethyl methacrylate (PMMA) [18]. Another study demonstrated the fabrication of 60 nm silver nanodisks on a sapphire substrate, also coated with PMMA [19].…”
Section: Purposementioning
confidence: 99%
“…Electron beam lithography (EBL), a technique renowned for its precision in crafting custom designs on lithographic resists, plays a crucial role in this process. In the context of LPSIM, EBL has been employed to create hexagonal arrays of silver nanodisks on glass substrates, subsequently coated with a thin layer of polymethyl methacrylate (PMMA) [18]. Another study demonstrated the fabrication of 60 nm silver nanodisks on a sapphire substrate, also coated with PMMA [19].…”
Section: Purposementioning
confidence: 99%
“…The spatial light modulator assisted [98][99][100][101][102] SIM system makes image acquisition speed faster than classical grating based system. Multiple Moiré illumination patterns [103][104][105] helps to achieve multi-fold resolution improvement over the widefield limit; this is similar to nonlinear SIM approach having higher harmonics without the requirement of special fluorophores. Periodic 2D pattern (e.g.…”
Section: D Simmentioning
confidence: 99%
“…Caldero´n-Hermosillo et al [5] used the moiré technique on complex amplitude of the Spatial Light Modulator. The moiré technique has also been applied to the structural illumination microscopy [6,7]. Yu et al [8,9] worked on the visible moiré patterns and the influence of different grating frequencies on the resulting moiré patterns.…”
Section: Literature Surveymentioning
confidence: 99%